2005
DOI: 10.1086/429622
|View full text |Cite
|
Sign up to set email alerts
|

Genital Tract Shedding of Herpes Simplex Virus Type 2 in Women: Effects of Hormonal Contraception, Bacterial Vaginosis, and Vaginal Group B Streptococcus Colonization

Abstract: The present study identifies hormonal contraceptive use, bacterial vaginosis, and high-density vaginal GBS colonization as risk factors for genital tract shedding of HSV-2 in women. Because hormonal contraceptives are used by millions of women worldwide and because bacterial vaginosis and vaginal GBS colonization are common vaginal conditions, even modest associations with HSV-2 shedding would result in substantial attributable risks for transmission of the virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 26 publications
3
80
2
2
Order By: Relevance
“…Epidemiologic studies have demonstrated that BV is associated with a markedly increased risk for acquisition of sexually transmitted infections (STIs) (3)(4)(5)(6), including HIV (5,(7)(8)(9)(10), and the development of pelvic inflammatory disease (PID) (11). Transmission of STIs is also associated with BV, since BV increases viral replication and vaginal shedding of HIV-1 (7,(12)(13)(14) and herpes simplex virus type 2 (HSV-2) (15). During pregnancy, BV has been linked to late fetal loss, and 10%-30% of pregnant women with BV give birth prematurely, although there is a lack of consistent evidence that treatment of BV reduces the risk of preterm delivery (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have demonstrated that BV is associated with a markedly increased risk for acquisition of sexually transmitted infections (STIs) (3)(4)(5)(6), including HIV (5,(7)(8)(9)(10), and the development of pelvic inflammatory disease (PID) (11). Transmission of STIs is also associated with BV, since BV increases viral replication and vaginal shedding of HIV-1 (7,(12)(13)(14) and herpes simplex virus type 2 (HSV-2) (15). During pregnancy, BV has been linked to late fetal loss, and 10%-30% of pregnant women with BV give birth prematurely, although there is a lack of consistent evidence that treatment of BV reduces the risk of preterm delivery (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…BV has several severe consequences including increasing the risk of preterm birth, miscarriage and pelvic inflammatory disease [14][15][16]. BV also increases the risk of infection with human immunodeficiency virus (HIV) and herpes simplex virus type 2 [13,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A lack of lactobacilli in the vaginal tract may disturb the balance of the microbial flora and can lead to bacterial vaginosis via overgrowth of anaerobic bacteria (5). Women whose genital microbial florae are dominated by lactobacilli also have lower risks of contracting sexually transmitted diseases, such as those caused by human immunodeficiency virus (HIV), herpes simplex virus type 2, human papillomavirus (HPV), and Chlamydia trachomatis (5)(6)(7). In addition, colonization by lactobacilli has been shown to be correlated with lower risks for pelvic inflammatory disease and pregnancy-related complications (1,8).…”
mentioning
confidence: 99%